2009
DOI: 10.3324/haematol.2009.011429
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of pre-transplantation transfusion history and secondary iron overload in patients with myelodysplastic syndrome undergoing allogeneic stem cell transplantation: a GITMO study

Abstract: BackgroundTransfusion-dependency affects the natural history of myelodysplastic syndromes. Secondary iron overload may concur to this effect. The relative impact of these factors on the outcome of patients with myelodysplastic syndrome receiving allogeneic stem-cell transplantation remains to be clarified. Design and MethodsWe retrospectively evaluated the prognostic effect of transfusion history and iron overload on the post-transplantation outcome of 357 patients with myelodysplastic syndrome reported to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
125
4
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(136 citation statements)
references
References 29 publications
(40 reference statements)
5
125
4
2
Order By: Relevance
“…We and other groups have previously demonstrated that high serum ferritin levels before HSCT may reduce OS and EFS after HSCT. [1][2][3][4][5][6][7][8][21][22][23][24] To the best of our knowledge, the present study is the first to confirm these findings using a large prospective cohort.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We and other groups have previously demonstrated that high serum ferritin levels before HSCT may reduce OS and EFS after HSCT. [1][2][3][4][5][6][7][8][21][22][23][24] To the best of our knowledge, the present study is the first to confirm these findings using a large prospective cohort.…”
Section: Discussionsupporting
confidence: 77%
“…Recent studies have demonstrated that pretransplant iron overload, defined as elevated serum ferritin levels, is associated with worse OS, disease-free survival and non-relapse mortality (NRM) and with an increased risk of infection in patients undergoing allogeneic HSCT. [1][2][3][4][5][6][7][8][9] Liver dysfunction caused by iron overload 10 and neutrophil dysfunction with an increase in non-transferrin-bound iron levels 11,12 may have a negative impact on HSCT outcomes. However, most previous studies involved retrospective analyses of patients with heterogeneous diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the patients with MDS become transfusion dependent. Secondary iron overload from frequent red blood cell transfusions and poor iron incorporation into red blood cells (RBCs) is associated with poor survival in these patients [2]- [4]. Transfusion requirement has been recently recognized as an independent prognostic factor for survival in MDS patients [5].…”
Section: Discussionmentioning
confidence: 99%
“…27 Pretransplantation serum ferritin may have significant prognostic value in patients with MDS undergoing myeloablative allogeneic HSCT, inducing a significant increase of non-relapse mortality. 5 Thus, iron status could be considered in transplantation decision-making in MDS. Iron burden might influence toxic-infectious complications during the first 3 months after transplant in auto-transplanted patients.…”
Section: Discussionmentioning
confidence: 99%
“…4 Iron overload or hyperferritinemia irrespective of body iron status may have detrimental effects on the transplantation procedures. [5][6][7][8] Iron overload is associated with free radical generation leading to tissue damage. 9 There is also a possibility that the adverse prognostic impact of pre-transplant hyperferritinemia might be ascribed to other precipitating factors in addition to the iron overload.…”
Section: Introductionmentioning
confidence: 99%